Tradisi Mendo’akan Orang Non Muslim Menurut Konsep Fiqih (Urf) dan Ushul Fiqh - Nurul Afifah (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2018)
Society has a way of life in accordance with norms or values that are believed. So if there are persons leave a tradition that has been well appreciated will be considered to have violated the prevailing norms. The problem in this research is the tradition of praying for non-Muslims conducted by Muslims Metro Lampung. Whereas in the Qur'an letter at-taubah verses 113-114 it is clearly mentioned that it is forbidden praying for non-muslim even though the person is her parentas. So this research is done aims to find out how the tradition of praying for non muslims according to the concept of fiqh ('Urf) and ushul fiqh.In the concept of fiqh and ushul fiqih traditions that apply in a community environment called 'urf. The existence of 'urf itself can be used as a juridical foundation that produces the provisions of sharia law independently. In its application, not all customs can be used as the basis for the stipulation of a law (al-'Adah Muhakkamah) provision, but there are provisions that must be fulfilled, namely: ‘urf does’nt conflict with al-Qur’an, ‘urf is constant and majority, formed earlier than its use as a legal ground. And there is no word or deed contrary to the substance that turns away from custom.Tradition of praying for non muslims in Metro Lampung including 'Urf. If viewed from the aspect of the product of his deeds including al-'Urf al-Amali. From the aspect of his appreciation coverage including al-'Urf al-Khas. and if seen from the aspect of determination or recognition of shari'ah including al-'Urf al-Fasid. Keywords: tradition, society, non-muslim, 'urf